High-speed Rail Network and Changing Industrial Dynamics in Chinese Regions. (September 2019) - Zhu, Shengjun; Wang, Chong; He, Canfei
High-speed railway (HSR) network can significantly reduce the transport cost of people and facilitate interregional knowledge spillovers. It may thus affect regional industrial dynamics. By employing the industrial relatedness indicator, this article shows that regional industrial dynamics is path dependent in China. It further adopts several classical accessibility indicators to capture the network characteristics of transport infrastructure and the accessibility of Chinese cities in the HSR network. In response to the endogeneity issue, we design an instrumental variable based on historic transport network. Another econometric strategy is to include only two groups of cities in the sample: cities with existing HSR stations and cities with planned HSR stations. The empirical results suggest that high accessibility in the HSR network not only pushes forward new industry creation but also enables regions to be more pathbreaking and diversify into less related industries.